Almost Periodic Solution of a Multispecies Discrete Mutualism System with Feedback Controls - Hui Zhang; Feng Feng; Bin Jing; Yingqi Li (Discrete Dynamics in Nature and Society)
We consider an almost periodic multispecies discrete Lotka-Volterra mutualism system with feedback controls. We firstly obtain the permanence of the system by utilizing the theory of difference equation. By means of constructing a suitable Lyapunov function, sufficient conditions are obtained for the existence of a unique positive almost periodic solution which is uniformly asymptotically stable. An example together with numerical simulation indicates the feasibility of the main result.